2017
DOI: 10.2337/db16-0916
|View full text |Cite
|
Sign up to set email alerts
|

Neurturin and a GLP-1 Analogue Act Synergistically to Alleviate Diabetes in Zucker Diabetic Fatty Rats

Abstract: Neurturin (NRTN), a member of the glial-derived neurotrophic factor family, was identified from an embryonic chicken pancreatic cDNA library in a screen for secreted factors. In this study, we assessed the potential antidiabetic activities of NRTN relative to liraglutide, a glucagon-like peptide 1 receptor agonist, in Zucker diabetic fatty (ZDF) rats. Subcutaneous administration of NRTN to 8-week-old male ZDF rats prevented the development of hyperglycemia and improved metabolic parameters similar to liragluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The injection of NRTN in a diabetic rat model prevents the development of hyperglycemia, and reduces fasting glucose levels and the deterioration of metabolic parameters. However, it is not clear how NRTN mediates its metabolic activity to prevent hyperglycemia [75]. Diabetes can also result in the loss of enteric neurons leading to gastrointestinal dysfunction.…”
Section: In Diabetesmentioning
confidence: 99%
“…The injection of NRTN in a diabetic rat model prevents the development of hyperglycemia, and reduces fasting glucose levels and the deterioration of metabolic parameters. However, it is not clear how NRTN mediates its metabolic activity to prevent hyperglycemia [75]. Diabetes can also result in the loss of enteric neurons leading to gastrointestinal dysfunction.…”
Section: In Diabetesmentioning
confidence: 99%
“…Experiments utilize human neuroblastoma cell line, TGW (TGW-SRE-Luc, clone 42, JCRB0618, originally from the Japanese Collection of Research Bioresources), stably expressing a reporter gene construct containing a luciferase gene under control of repetitive Serum Response Elements as descibed earlier (34). The assay is carried out in Collagen I coated 96 well plates (Becton Dickinson Labware) using Neolite High Sensitivity Luminescence Reporter Gene Assay System (PerkinElmer).…”
Section: Activity Assessment Of Neurturin Mutantsmentioning
confidence: 99%
“…NRTN induced signalling has been shown to provide trophic support to neurons (5) and is especially important in guiding the development and distribution of parasympathetic, sensory and enteric innervations (32). The effects on cell survival have also indicated the potential of NRTN in treatment of asthma (33) and, recently, in diabetes, as it has been shown to prevent the development of hyperglycemia and increase β-cell mass in diabetic rats (34). Despite the therapeutic relevance of NRTN and other members of the GDNF protein family, it is still not clear how the receptor complexes are formed, how selectivity between the co-receptors is achieved and how RET is activated.…”
mentioning
confidence: 99%
“…All the later data suggest the important role of the neuronal gut brain axis in the efficiency of anti-diabetic treatments. Furthermore, a recent study demonstrated that a co-treatment with neurturin, a glial cell-line derived neurotrophic factor, with a GLP-1 analogue improved the diabetic state of Zucker fatty rats [144].…”
Section: Current Treatment Of Type 2 Diabetes: How Can We Improve Thementioning
confidence: 99%